Lattice strain gradient influences on steady-state rates of hydrogen permeation through membranes - Lewis, F.A.; Tong, X.Q.; Kandasamy, K. (My University, 1993)
Permeation rate observations are reported which demonstrate the influence of lattice expansive strain gradients in producing nonlinear hydrogen concentration profiles through cross-sections of hydrogen diffusion membranes under "steady-state" conditions of hydrogen permeation.